Germination Performance of Cowpea (Vigna Unguiculata) Seeds Treated with Entomopathogenic Isolates - Nwosu, Onyeka Kingsley; Ogbadoyi, Emmanuel Olofu; Babayi, Hausatu; Olayemi, Israel Kayode (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The use of bio-control measures as alternative to chemical pesticides is increasingly encouraged on the basis of food safety as chemical pesticides are dangerous to human health. However, limited attention is paid to the impact of these bio-control measures on the germination performance of treated seeds. In this study, the germination performance of stored cowpea seeds treated with isolates of entomopathogens (Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringensis) usually used as bio-pesticides was investigated. The pure isolates were subjected to liquid fermentation technology using sucrose water as the substrate and the liquid medium. The isolates obtained through liquid fermentation were also inoculated into talc powder as solid medium. The germination viability of the cowpea seeds treated with the liquid and solid mediums of the isolates and stored for ten (10) weeks was determined using the standard germination test adopting the seed germination vigour (SGV) and the seed germination ability (SGA) as parameters. The study revealed that the cowpea seed treatment with the isolates in their liquid and solid mediums showed no significant impact on SGV and SGA when compared with control at the end of 1st and 5th week storage post-treatment. However a significant effect was seen at the end of 10th week storage post-treatment with the liquid medium of Verticillium lecanii showing better germination performance (SGV=58.33±1.67 and SGA=71.67±3.33) among other liquid medium isolates when compared with the control (SGV=68.33±1.67 and SGA=80.00±2.89), and the solid medium of Bacillus thuringensis revealing better germination performance (SGV=58.33±3.33 and SGA=71.67±1.67) among other solid isolates when compared with the control (SGV=68.33±1.67 and SGA=80.00±2.89). This study concludes that isolates of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringensis do not reduce germination performance of cowpea seeds when used as bio-control against cowpea storage pest. However, at longer storage post-treatment of cowpea seeds with the isolates, the germination performance may be reduced.